Empowering Inclusive Design Education in the Pensil Kertas Community Through a Text-based Prototype and Digital Approach - Muhamad Nugraha; Ranti Rachmawanti; Lira Anindita Utami (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2025)
Since 2009, Pensil Kertas Community has lived in Bandung city, This community supports inclusive education in design with training programs, visual, and collective drawing activities from elementary to out-of-college learners. Major challenges when they hiatus from 2019 to 2024. This paper explores the gap challenges from traditional communities, process of the finding digital journey through a text-based prototype and digital solutions to help the creative ecosystem in this community. Aligned with the Sustainable Development Goals (SDGs) point 4 (quality education) and 11(sustainable cities), this study adopts a participatory design approach as its design process. enhance interactivity through digital media.